The Disappearance/Virtualisation of Graffiti and Street Art: From Urban to Institutional to Virtual Space - Brita, Tania Di (Street Art & Urban Creativity, 2020)
The subject of this essay is the presentation and reflection of curatorial challenges related to the exhibiton of graffiti and street art. The curatorial practices of graffiti and street art has undergone several changes over the past decades: from the streets to the institutionalisation and commercialisation to virtualisation. In particular, the essay is examining curatorial practises in three main areas, the streets, the institutions and finally the augmented and virtual space. Due to the development of ICT and digitalization the possibilities of curating seem countless. However, within these developments there is also a downside. What if all unsanctioned graffiti and street art suddenly have ‘no space’, nor in the virtual nor in the real world, where neoliberal cities desire homogeneity, segregation and 24/7 surveillance? Can unsanctioned art even exist in the virtual reality? Can it still be called ‘unsanctioned’ or ‘illegal’? The possibilities of multiple layers of reality as well as the thread of the disappearance stand very are very close by each other. It is the time to think about where and how which require novel perspectives and appropriate formats on how to reinforce this unique cultural expression in public.